An Analysis of Language Styles Used by the Main Characters in the Dialogues in Business Proposal Series - Simamora, Riris Mutiara Paulina; Sherina, Sherina (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2022)
Language styles emerge as one of the sociolinguistics subfields that focus on the way people speak based on the formality scale of the social life that people have. This research, entitled "An Analysis of Language Styles used by the main characters in the dialogues in the "Business Proposal" series", is a thesis that aims to show the difference in language styles using Martin Joos's (1967) theory from his book "The Five Clocks" as well as the social factors theory by Janet Holmes (2013) that influence the usage of language styles. The method used in this thesis is a qualitative method, and the data source is a series from South Korea with the title "Business Proposal." The researchers have found that there are 144 dialogues in 10 episodes of the series that consist of 0 dialogues in frozen style, 3 dialogues in formal style, 80 dialogues in consultative style, 55 dialogues in casual style, and 6 dialogues in intimate style. After that, to conclude this research, the researchers discovers that the usage of language styles by the main characters is caused by social factors such as participants’ age and position, settings of home and office, jokes and serious topics, and functions in sharing information and asking something.AbstrakGaya bahasa muncul sebagai salah satu subbidang sosiolinguistik yang berfokus pada cara seseorang berbicara berdasarkan skala formalitas kehidupan sosial yang dimiliki. Penelitian yang berjudul "An Analysis of Language Styles used by the main characters in the dialogues in the "Business Proposal series" ini merupakan penelitian yang bertujuan untuk menunjukkan perbedaan gaya bahasa menggunakan teori Martin Joos (1967) dari bukunya "The Five Clocks" serta teori faktor sosial oleh Janet Holmes (2013) yang mempengaruhi penggunaan gaya bahasa. Metode yang digunakan dalam tesis ini adalah metode kualitatif, dan sumber data yang digunakan adalah serial dari Korea Selatan dengan judul " Business Proposal." Dari hasil penelitian ditemukan 144 dialog dalam 10-episode yang terdiri dari 3 dialog gaya formal, 80 dialog dalam gaya konsultatif, 55 dialog dalam gaya kasual, dan 6 dialog dalam gaya intimate. Seteah melakukan analisis, disimpulkan bahwa penggunaan gaya bahasa oleh karakter utama disebabkan oleh faktor sosial seperti usia dan posisi tokoh, lokasi rumah dan kantor, lelucon dan topik serius, dan fungsi dalam berbagi informasi dan saat menanyakan sesuatu.